IDENTIFIKASI BAKTERI DAN KAPANG PADA PROSES PRE-TREATMENT FESES SAPI POTONG DAN TANDAN KOSONG KELAPA SAWIT - Safitry, Rania Zabina; Marlina, Eulis Tanti; Harlia, Ellin (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The abundance of livestock and agricultural waste needs special attention, especially in its processing. One of the largest wastes generated from the livestock sub-sector is beef cattle feces; in the agricultural sub-sector, empty fruit bunches are produced (EFB). In this study, beef cattle feces and empty fruit bunches were decomposed for 14 days to degrade organic matter into raw materials for second-generation bioethanol. This study aimed to identify bacteria and molds that play a role in the decomposition of beef cattle feces and EFB. The research conducted used a qualitative-descriptive method. This study identified microorganisms in the biological pre-treatment process on days 1st, 7th, and 14th. The identification of bacteria and molds was done macroscopically and microscopically. The genus of bacteria found in biological pre-treatment is Bacillus. There are 3 genera of molds found in biological pre-treatment including Aspergillus, Trichoderma, and Mucor. These genera have cellulotic and lignolytic potential in fiber degradation in biological pre-treatment.